2022
DOI: 10.3390/cells11233786
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Nutraceutical Activation of Rejuvenation, Geroprotection and Cytoprotection: Proofs of Concept

Abstract: Aging is a process associated with life [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…In developing a basic approach and defining anti-aging and rejuvenation activity, it is possible to start from the human as a whole, organs and functional sub-systems, or from the cell level. Indeed, a broad literature is available on the cell-level anti-aging and rejuvenation strategies, methods and studies ( [31][32][33][34][35][36][37][38] can be suggested as more general publications and reviews relevant to the discussed topic). Large number of researchers directly correlate human aging to the processes at the cell level [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…In developing a basic approach and defining anti-aging and rejuvenation activity, it is possible to start from the human as a whole, organs and functional sub-systems, or from the cell level. Indeed, a broad literature is available on the cell-level anti-aging and rejuvenation strategies, methods and studies ( [31][32][33][34][35][36][37][38] can be suggested as more general publications and reviews relevant to the discussed topic). Large number of researchers directly correlate human aging to the processes at the cell level [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%